Undeserving Welfare Recipients from the State’s Point of View in Québec, Canada - Gagnon Poulin, Éric (Anthropologica, 2022)
With the adoption of the “Act to combat poverty and social exclusion” (Act 112) in 2002, Québec had to present three action plans “[…] to guide the Government and Québec society as a whole toward a process of planning and implementing actions to combat poverty and counter social exclusion and strive toward a poverty-free society” (Québec 2002, 2). To achieve this important goal, one of the state’s strategies has been to reinforce already existing employment incentives for people considered “fit” for work and promote a more flexible workforce. This article questions the “worth” of unemployed welfare recipients “without limited capacity” for employment in the current neoliberal labour market. This research demonstrates that their “value” is directly linked to their ability to work and productivity in the state discourse on the fight against poverty, influencing thereafter the popular understanding of this polysemous socioeconomic phenomenon. Mainly by analyzing the three action plans to combat poverty and interviewing informants enrolled in employment incentives in the area of Chaudière-Appalaches, this project also underlines how the workfare model collaborates in the reproduction of poverty and the proliferation of precarious jobs in our globalized economies.